(Ni, Co)Se2/NiCo‐LDH Core/Shell Structural Electrode with the Cactus‐Like (Ni, Co)Se2 Core for Asymmetric Supercapacitors. Issue 3 (17th December 2018) - Li, Xin; Wu, Haijun; Guan, Cao; Elshahawy, Abdelnaby M.; Dong, Yangtao; Pennycook, Stephen J.; Wang, John
Abstract: Supercapacitors (SCs) have been widely studied as a class of promising energy‐storage systems for powering next‐generation E‐vehicles and wearable electronics. Fabricating hybrid‐types of electrode materials and designing smart nanoarchitectures are effective approaches to developing high‐performance SCs. Herein, first, a Ni‐Co selenide material (Ni, Co)Se2 with special cactus‐like structure as the core, to scaffold the NiCo‐layered double hydroxides (LDHs) shell, is designed and fabricated. The cactus‐like structural (Ni, Co)Se2 core, as a highly conductive and robust support, promotes the electron transport as well as hinders the agglomeration of LDHs. The synergistic contributions from the two types of active materials together with the superior properties of the cactus‐like nanostructure enable the (Ni, Co)Se2 /NiCo‐LDH hybrid electrode to exhibit a high capacity of ≈170 mA h g −1 (≈1224 F g −1 ), good rate performance, and long durability. The as‐assembled (Ni, Co)Se2 /NiCo‐LDH//PC (porous carbon) asymmetric supercapacitor (ASC) with an operating voltage of 1.65 V delivers a high energy density of 39 W h kg −1 at a power density of 1650 W kg −1 . Therefore, the cactus‐like core/shell structure offers an effective pathway to engineer advanced electrodes. The assembled flexible ASC is demonstrated to effectively power electronic devices. Abstract : A (Ni, Co)Se2 /NiCo‐LDH electrode with core/shell structure is developed for hybrid capacitors. The conductive and robust (Ni, Co)Se2 core exhibits a unique 3D cactus‐like architecture, which facilitates the electron transport, and simultaneously buffers the aggregation of active sites. The smartly designed bimetallic composition and 3D cactus‐like structure are synergized to deliver excellent electrochemical performance.